Policies and measures for energy efficiency improvement at households: A bibliometric analysis - Streimikiene, Dalia; Kyriakopoulos, Grigorios L.; Ślusarczyk, Beata; Stankuniene, Gintare (Center of Biomass & Renewable Energy, Diponegoro University, 2024)
Recently, governmental subsidies have led to increased renewable energy adoption and household CO2 emissions reduction. However, energy efficiency improvement and greenhouse gas emission reduction potential in households’ sector are not yet fully realized. Decision-making by individuals is also a crucial factor in adopting energy-efficient and renewable energy technologies, which is why this study analyses some important behavioral change-linked issues. This study also focuses on various policies and measures to achieve energy efficiency improvements in households, such as use of renewable energy sources, renovation of residential buildings, use of energy efficient appliances etc. The methodology of the study contains a bibliometric analysis in the field of energy efficiency at households, covering the years of publication 2010-2023 and organizing all documents into 9 classifications. Among them 6 classifications have been further considered: Citation analysis; Authors’ networks; High impact journals of publishing; Knowledge mapping of co-authorship collaboration among institutions; Co-authorship among countries; Keywords concurrence analysis. Following a systematic literature review the bibliometric findings reveal the steady increase of literature production in the field of energy efficiency at households, showing also the pivotal role of institutions among developed and industrialized economies. Moreover, there is a densely and steadily growing network of keywords reported, implying the thematic expansion of this topic from the modelling-pilot scales towards the real world and in field applications. Finally, identified research constraints of energy efficiency improvement are that of: high costs, lack of information and knowledge, low priority to environmental and climate change mitigation concerns, and resistance to behavioral change.